Oxigenioterapia hiperbárica em cães e gatos: respostas comportamentais, temperatura retal e parâmetros hematológicos - Antunes, Bernardo Nascimento (2024)
Hyperbaric oxygen therapy (HBOT) is highlighted as an adjuvant therapy in the healing process of complicated wounds, with potential use in the preservation and/or preparation of the surgical bed preoperatively. Experimental evidence also suggests the benefits of HBOT when used as a preconditioning stimulus in the setting of ischemia/reperfusion injury. However, more studies are still needed on its effects in healthy patients. The purpose of Study 1 of this Thesis was to evaluate the influence of behavior on the variation in rectal temperature in dogs and cats undergoing HBOT. The purpose of Study 2 was to evaluate the effects of an HBOT session on hematological and hemostatic parameters in healthy bitches undergoing laparoscopic-assisted ovariohysterectomy (OVH). In article 1, clinical data from 217 HBOT sessions with 2 to 2.5 atmospheres absolute (ATA), under 30- or 45-minute therapy protocols, in 29 canine and 13 feline patients were reviewed. Data on clinical behavior, initial rectal temperature, final rectal temperature and variation in rectal temperature for each patient were analyzed, as well as chamber’s temperature, oxygen concentration and humidity and flow rate during each session. Dogs and cats undergoing HBOT may present reduction in rectal temperature, though not affecting clinical behavior during the session. Selftrauma during HBOT may occur as a major adverse event in cats. Regarding article 2, 30 healthy adult bitches were randomly assigned into one of three groups of 10 animals each one, as follows: GHC (submitted to HBOT with 2 ATA for 45 minutes, followed by laparoscopicassisted OVH); GH (submitted to HBOT with 2 ATA for 45 minutes); and GC (submitted to laparoscopic-assisted OVH). Assessments included CBC, renal and hepatic serum biochemistry, prothrombin time (PT), activated partial thromboplastin time (APTT), buccal mucosal bleeding time (BMBT) and the area of the bloodstain on hygroscopic paper. After surgery, neutrophilia (p≤ 0.0039) occurred in both GHC and GC groups. GC group showed an increase in total leukocyte count (p= 0.0238) and GHC group presented a reduction in lymphocyte count (p= 0.0115). There was a reduction in PT and APTT after HBOT in GHC group (p≤ 0.0412). After HBOT, there was no significant difference between the groups for PT (p≥ 0.4359), as well as between the GHC and CG groups for BMBT (p= 0.6769) and for the area of the bloodstain on hygroscopic paper (p= 0.1697). We concluded that one session of HBOT was not able to induce significant effects on BMBT and the volume of blood drained during this test in healthy female dogs. However, a reduction in PT and APTT is expected for these patients, immediately after the HBOT session, as well as in lymphocyte count, when followed by laparoscopic-assisted OVH.